Impact of Sjögren’s disease on quality of sexual life using the Qualisex score - Eric Hachulla; Xavier Mariette; Jacques-Eric Gottenberg; Philippe Dieude; Aleth Perdriger; Emanuelle Dernis; Marion Couderc; Raphaele Seror; Gaetane Nocturne; Rakiba Belkhir; Valérie Devauchelle-Pensec; Veronique Le Guern; et al. (RMD Open, 2025)
Objective This study aimed to assess the impact of Sjögren disease (SjD) on the quality of sexual life and its determinants using the Qualisex questionnaire.Methods The Qualisex questionnaire was administered to participants within the ASSESS cohort, a French national multicentric prospective cohort of individuals with SjD. Patients’ characteristics and psychometric evaluations were also collected.Results Among the 395 patients of the cohort, 92 (23%) completed the questionnaire, with a median age of 56 (44–59) years and a female ratio of 92% (85/92). The median Qualisex score was 3.4 (1.1–5.9).Comparing the first and last quartiles of the Qualisex score, a worst sexual satisfaction was associated with older age (median (IQR) 58 (52–65) vs 52 (41–56) years, p=0.005), higher EULAR Sjögren’s disease Patient Reported Index (ESSPRI) (6.8 (5.7–7.7) vs 4.3 (2.8–5.3), p<0.0001) lower SF-36 mental and physical scores (respectively, 43 (38–46) vs 49 (47–53), p=0.0035 and 31 (29–35) vs 35 (30–37), p=0.035), higher Depression and Anxiety scores (HADS) (respectively, 9 (7–11) vs 2 (1–4), p<0.0001 and 11 (8–14) vs 7 (4–10), p=0.006). Interestingly, EULAR Sjögren’s disease Disease Activity Index (ESSDAI) score did not differ significantly (4 (1–10) vs 2.5 (1.8–4), p=0.35). In a multivariable analysis, the Qualisex score remained strongly associated with a higher HADS depression score and, to a lesser extent, with a higher ESSPRI. The inability to obtain a score was associated with older age.Conclusion In SjD patients, sexual satisfaction assessed with the Qualisex score, was strongly associated with depression and, to lesser extent, with ESSPRI, but not with systemic activity.